Subtle Differences in the Representation of Consumer Dynamics Have Large Effects in Marine Food Web Models - Flynn, Kevin J.; Speirs, Douglas C.; Heath, Michael R.; Mitra, Aditee (Frontiers in Marine Science, 2021)
Projecting ocean biogeochemistry and fisheries resources under climate change requires confidence in simulation models. Core to such models is the description of consumer dynamics relating prey abundance to capture, digestion efficiency and growth rate. Capture is most commonly described as a linear function of prey encounter or by rectangular hyperbola. Most models also describe consumers as eating machines which “live-to-eat”, where growth (µ) is limited by a maximum grazing rate (Gmax). Real consumers can feed much faster than needed to support their maximum growth rate (µmax); with feeding modulated by satiation, they “eat-to-live”. A set of strategic analyses were conducted of these alternative philosophies of prey consumption dynamics and testing of their effects in the StrathE2E end-to-end marine food web and fisheries model. In an experiment where assimilation efficiencies were decreased by 10%, such as might result from a change in temperature or ocean acidity, the different formulation resulted in up to 100% variation in the change in abundances of food web components, especially in the mid-trophic levels. Our analysis points to a need for re-evaluation of some long-accepted principles in consumer-resource modelling.